The Differences on Cholesterol Levels was Centrifuged Samples after Freezed for 30 Minutes and 2 Hours - Prarastri, Chalista; Saktiningsih, Hari (Jurnal Biologi Tropis, 2024)
Cholesterol is one type of fat commonly recognized by the public that has a function for the formation of a number of important components. The pre-analytical stage accounts for 68% of errors in the laboratory, one of which is in the sample processing section, namely the delayed serum preparation process, this can affect the results that are not appropriate. The purpose of this study was to determine the difference in cholesterol levels in centrifuged samples after freezing 30 minutes and 2 hours. This type of research is experimental research. This research was conducted at the Clinical Chemistry Laboratory of the National College of Health Sciences. The sampling technique used was quota sampling. The samples used were serum consisting of 2 handling groups from 21 respondents. The study used SPSS 25.0 data analysis with paired T test where previously data normality test was conducted. Data were tested with data normality using the Shapiro-wilk test because the sample was less than 50. The results of the study in the paired T test sig (2-tailed) is 0.014 (p value>0.05) can be concluded that there are differences in cholesterol levels in centrifuged samples after freezing 30 minutes and 2 hours.